Pemanfaatan Media Digital dalam Proses Pembelajaran Ilmu Pengetahuan Sosial (IPS) Terpadu di Sekolah Dasar Kak Seto - Siregar, Andyoda; Sumantri, Pulung (Medan Resource Center, 2024)
The use of digital media in the integrated Social Sciences (IPS) learning process at Kak Seto Elementary School has become an important topic in the world of education. Digital technology has changed the way we learn, and the use of digital media in the classroom has the potential to increase the effectiveness of integrated social studies learning. This study aims to explore the benefits and challenges in implementing digital media in integrated social studies learning at Kak Seto Elementary School. This research uses a qualitative approach by collecting data through interviews with teachers, classroom observations, and analysis of related documents. The research results show that the use of digital media in integrated social studies learning at Kak Seto Elementary School has provided a number of benefits, including increased student engagement, increased understanding of concepts, and increased learning motivation. Apart from that, digital media also allows teachers to present material in a more interesting and varied way. However, there are several challenges that need to be overcome in implementing digital media, such as limited technological accessibility, the need for more in-depth teacher training, and careful monitoring of digital media use so that it does not interfere with learning. The results of this research can be a basis for developing better strategies in utilizing digital media in the integrated social studies learning process at the elementary level. Therefore, cooperation is needed between teachers, schools and related parties in effectively integrating digital media in integrated social studies learning.